2009
DOI: 10.1016/j.fertnstert.2008.01.108
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide metabolite production in the human preimplantation embryo and successful blastocyst formation

Abstract: Eleven patients underwent controlled ovarian hyperstimulation yielding seventy-two embryos for evaluation. Mean nitric oxide metabolite (NOx) levels in the insemination media (IM) were 2.6 times higher in embryos that progressed to blastocysts by culture day (CD) 5 than those that did not (p=0.009). A comparison of the ROC curves between morphologic predictors and NOx levels revealed a trend toward a stronger association of IM NOx with blastocyst formation.Improvements in in vitro fertilization (IVF) outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Nitric oxide regulates early-stage embryonic development in mice ( Chen et al, 2001 , Tranguch et al, 2003 ) and humans ( Lipari et al, 2009 ). Nitric oxide synthases 3 mRNA and protein are abundant in trophectoderm and endoderm of peri-implantation ovine conceptuses, whereas NOS1 mRNA and protein are expressed very weakly ( Gao et al, 2009e ).…”
Section: Arginine and Development Of The Ovine Conceptusmentioning
confidence: 99%
“…Nitric oxide regulates early-stage embryonic development in mice ( Chen et al, 2001 , Tranguch et al, 2003 ) and humans ( Lipari et al, 2009 ). Nitric oxide synthases 3 mRNA and protein are abundant in trophectoderm and endoderm of peri-implantation ovine conceptuses, whereas NOS1 mRNA and protein are expressed very weakly ( Gao et al, 2009e ).…”
Section: Arginine and Development Of The Ovine Conceptusmentioning
confidence: 99%
“…Oxidative stress is involved in numerous signal transduction pathways in cellular physiology and pathology (17,18) and in oxidative processes, which may be reflected in the culture media of the growing embryo during early development. Lipari et al (19) found an association between nitric oxide (a cytokine and pro-oxidant, involved in cellular physiology) metabolite production in the insemination media in IVF and successful blastocyst formation. The addition of certain nutrients to the culture media recently has been shown to improve the oxidative state of the early embryo (20,21).…”
mentioning
confidence: 99%
“…On the one side, Battaglia et al (2003) [55] and Lipari et al (2009) [56] found an association between the nitric oxide metabolites released in the embryo culture media with blastocyst formation progression [55] together with the pregnancy rates [56]. In detail, the mean NO metabolites in the insemination media were 2.6 higher in embryos that progressed to the blastocyst stage on day 5 of culture compared with those that did not [55], while the NO metabolite concentrations of the culture medium of each embryo were higher in the pregnant-resulting patients than those who did not become pregnant [56]. On the contrary, no association was found between NO metabolite production in a culture medium with the embryo cleavage rate in the study of Gallinelli et al, 2009 [57].…”
Section: Nitric Oxide and Ivfmentioning
confidence: 99%